THE METHODOLOGICAL SIGNIFICANCE OF PHILOSOPHY IN SOCIAL DEVELOPMENT - Ismoilov Makhammadixon (Innovate Conferences, 2026)
This article explores the methodological importance of philosophy in the process of social development. Philosophy is examined not merely as a system of abstract ideas, but as a fundamental methodological framework that shapes human thinking, social consciousness, and approaches to understanding reality. The study analyzes the role of philosophical categories, principles, and methods in interpreting social processes, identifying patterns of development, and guiding scientific and practical activity. Particular attention is given to the relationship between philosophy and social sciences, as well as to the contribution of philosophical thinking to critical analysis, value orientation, and strategic decision-making in modern society. The article argues that philosophy plays a decisive role in ensuring the coherence, integrity, and reflexivity of social development in the context of globalization and rapid socio-technological change.
Keywords: philosophy, social development, methodology, social sciences, philosophical thinking, critical analysis, worldview, epistemology, value orientation.